Schiff Base Synthesis with a New Reliable Method and Investigation of Their Inhibition Effects on Glutathione S-Transferase and Cholinesterase Enzymes - Balci, Neslihan; Celik, Hulya; Turkan, Fikret; Celebioglu, Neslihan; Celik, Tuba; Bursal, Ercan (Wiley-V C H Verlag Gmbh, 2023)
The principle purpose of this study is to synthesize some Schiff base derivatives with a new microwave irradiation technique and investigate their enzyme inhibition effects. Related Schiff base compounds (1 a-1 h) were synthesized from 4-fluoro aniline and some substituted benzaldehyde derivatives (3 a-3 h). The chemical structures of Schiff bases were elucidated by various spectroscopic methods (H-1 NMR, C-13 NMR). The inhibitory effects of the synthesized compounds against acetylcholinesterase, butyrylcholinesterase and glutathione S-transferase were investigated. The in vitro enzyme study determined the best enzyme inhibitors for AChE, BChE, and GST enzymes as 3 h, 3 b, and 3 e compounds, respectively. The results were compared with the standard drugs tacrine for cholinesterase and ethacrynic acid for GST enzymes. Molecular docking results demonstrated the low binding energy values between -5.8 kcal/mol and -8.7 kcal/mol with hydrogen bonding, hydrophilic, and hydrophobic interactions at the active catalytic sites of the enzymes.
Keywords: Acetylcholinesterase; Butyrylcholinesterase; Enzyme Inhibition; Glutathione S-Transferase; Microwave Irradiation; Antimicrobial Activity; Biological-Activity; Acid; Antioxidant; Targets